ANALISIS PALEOANTROPOLOGI RANGKA R.X3 SITUS GILIMANUK KOLEKSI BALAI ARKEOLOGI DENPASAR - Syamyanti, Retka (Humanis, 2016)
Gilimanuk necropolis site is a site that is full of archaeological. Some of Archaeological findings are in form of burial and settlement which been found at the year 1962-2006. The skeleton of Gilimanuk Site could explain their people in the past. Gilimanuk’s Paleoanthropology also analized by its R.X3 which is collected by Balai Arkeologi Denpasar by observing the condition and size of the components of anatomy. This research is multidisiplim science and carried out systematically. The first stage in this research are observation, interviews, and literature. The second stage of the analysis using anthropometric analysis, antroposkopi, and comparison to determine the size of anatomical components R.X3 framework so that it can be identified race. The last step is drawing conclusions based on the data that has been collected to complete the information repertoire of human socio-cultural life Gilimanuk Site. The results of the analysis indicate that paleoanthropology order R.X3 this individual with the morphological characteristics of the Mongoloid race.
Keywords: Gilimanuk site,paleoanthropology, race